Figure 6 in Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy - Bianucci, Giovanni; Landini, Walter (Zenodo, 2006)
Figure 6. Zygophyseter varolai gen. et sp. nov. Left incomplete ear bones of the holotype (MAUL 229/1). A–F, periotic in (A) dorsal, (B) dorsomedial, (C, D) ventral, (E) medial and (F) anterior views. G, articulated periotic and tympanic bulla in lateral view; H–L, tympanic bulla in (H) dorsal, (J) ventral, (K) medial and (L) anterior views. D shows detail of the anterior process with the accessory ossicle not removed. : Published as part of Bianucci, Giovanni & Landini, Walter, 2006, Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy, pp. 103-131 in Zoological Journal of the Linnean Society 148 (1) on page 113, DOI: 10.1111/j.1096-3642.2006.00228.x, http://zenodo.org/record/5427349